Trend of the lipid profile in a cohort with severe hypercholesterolemia in Osona county (Barcelona, Spain), between 2009 and 2021 - Jordi Prat-Quinzaños; Joan Deniel-Rosanas; Pere Roura-Poch; Maria-Àngels Casas-Capdevila; Victor Farré-Guerrero (BMC Public Health)
Abstract Background Various studies confirm that the prevalence of dyslipidemia and other cardiovascular factors is high. Objective To evaluate the trend of the lipid profile (LP) in a cohort with severe hypercholesterolemia and its relationship with lipid-lowering treatment during the period 2009–2021. Methods Cross-sectional study carried out in the Osona county (Barcelona). Outpatients from the first period (2009–2011) who were aged between 25 and 65 years and had severe hypercholesterolemia were selected (n = 2,608). In a second period (2019–2021), these patients (n = 1,855) were followed up to evaluate the trend of LP and its relationship with lipid-lowering treatment. The Student’s T-test (paired data) was used to identify differences between observations from the two periods. Results Lipid-lowering treatment was prescribed to 61.9% of patients. The group of patients of the cohort improved the data of the mean results of the LP. Approximately 75% of cases were unable to establish their cholesterol and atherogenic fraction values. The prescription of lipid-lowering treatment in the cardiovascular disease group (CVD) was 80.9% vs 61.9% of the total cohort. Conclusion Three out of four cases failed to reduce the levels of LDL-C and non-HDL-C, recommended by the guidelines of scientific societies. Primary Care is the ideal framework to implement improvement strategies to control severe hypercholesterolemia, and it is therefore essential to strengthen it.